Aqueous Phase Phosphorescence: Ambient Triplet Harvesting of Purely Organic Phosphors via Supramolecular Scaffolding. Issue 52 (29th November 2018) - Kuila, Suman; Rao, K. Venkata; Garain, Swadhin; Samanta, Pralok K.; Das, Shubhajit; Pati, Swapan K.; Eswaramoorthy, Muthusamy; George, Subi J.
Abstract: Ambient solution and amorphous state room temperature phosphorescence (RTP) from purely organic chromophores is rarely achieved. Remarkable stabilization of triplet excitons is realized to obtain deep red phosphorescence in water and in amorphous film state under ambient conditions by a unique supramolecular hybrid assembly between inorganic laponite clay and heavy atom core substituted naphthalene diimide (NDI) phosphor. Structural rigidity and oxygen tolerance of the inorganic template along with controlled molecular organization via supramolecular scaffolding are envisaged to alleviate the unprecedented aqueous phase phosphorescence. Abstract : Aqueous phosphorescence : An unprecedented organic‐inorganic hybrid co‐assembly approach is proposed to obtain aqueous state as well as amorphous red‐emitting room temperature phosphorescence. Heavy‐atom effect in the NDI derivative along with its J‐aggregation enhance the intersystem crossing efficiency whereas rigid and oxygen tolerant laponite templates stabilize the triplets.